2020
DOI: 10.1002/cpt.1958
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Meta‐Analysis Validates a Role for S1PR1 in Microtubule Targeting Agent‐Induced Sensory Peripheral Neuropathy

Abstract: Microtubule targeting agents (MTAs) are anticancer therapies commonly prescribed for breast cancer and other solid tumors. Sensory peripheral neuropathy (PN) is the major dose‐limiting toxicity for MTAs and can limit clinical efficacy. The current pharmacogenomic study aimed to identify genetic variations that explain patient susceptibility and drive mechanisms underlying development of MTA‐induced PN. A meta‐analysis of genomewide association studies (GWAS) from two clinical cohorts treated with MTAs (Cancer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…In support of these ongoing clinical evaluations, a recent pharmacogenomic study revealed that patients with CINP have single nucleotide polymorphisms (SNPs) in a genomic region that regulates S1PR1 gene expression. These findings on genetic variations validate pharmacological studies and could explain patient susceptibility and drive mechanisms underlying CINP development [120]. Validation of the next generation of S1PR modulators requires preclinical and clinical trials (see Outstanding Questions).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 57%
See 1 more Smart Citation
“…In support of these ongoing clinical evaluations, a recent pharmacogenomic study revealed that patients with CINP have single nucleotide polymorphisms (SNPs) in a genomic region that regulates S1PR1 gene expression. These findings on genetic variations validate pharmacological studies and could explain patient susceptibility and drive mechanisms underlying CINP development [120]. Validation of the next generation of S1PR modulators requires preclinical and clinical trials (see Outstanding Questions).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 57%
“…Functional and competitive S1PR1 antagonists block morphine-induced hyperalgesia, tolerance, and dependence 2020 [83] Activation of S1PR2 following systemic administration of the selective S1PR2 agonist CYM-5478 attenuates cisplatin-induced neuropathic pain in rats 2020 [34] Patients with CINP have single nucleotide polymorphisms (SNPs) in a genomic region that regulate S1PR1 gene expression. These genetic variations validate pharmacological studies and could explain patient susceptibility to CINP development 2020 [120]…”
Section: Disclaimer Statementmentioning
confidence: 68%
“…A recent GWAS meta‐analysis of peripheral neuropathy following treatment of breast cancer patients with paclitaxel, nab‐paclitaxel or ixabepilone identified SNPs in the enhancer regions of S1PR1 encoding the G‐protein coupled receptor sphingosine‐1‐phosphate receptor 1 (S1PR 1 ) which were associated with an increased risk of developing CIPN 63 . In vitro validation studies utilizing FTY‐720 (fingolimod), a functional antagonist of S1P receptors, in combination with paclitaxel in an induced pluripotent stem cell (iPSC)‐derived sensory neuron model, demonstrated that S1PR1 inhibition confers neuronal protection against paclitaxel toxicity.…”
Section: Genetic Association Studies Provide Clues To the Molecular Mechanisms Underlying Mta‐induced Peripheral Neuropathymentioning
confidence: 99%
“…The most studied individual cancer drugs are methotrexate and paclitaxel, with six studies each. Six independent studies have investigated PGx of paclitaxel response; four of which studied the genomics of paclitaxel‐induced peripheral neuropathy and have implicated the gene S1PR1 in peripheral neuropathy risk 21 . Other frequently studied drugs are cisplatin and other platinum compounds (13 studies), and anthracyclines (5 studies).…”
Section: Most Studied Drugsmentioning
confidence: 99%